2019
DOI: 10.1111/1759-7714.13269
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of an elderly patient with an uncommon L861Q epidermal growth factor receptor mutation with low‐dose afatinib: A case report

Abstract: There are limited data on the clinical efficiency of afatinib in non-small cell lung cancer (NSCLC) patients with uncommon epidermal growth factor receptor (EGFR) mutations. Moreover, the efficacy and safety of afatinib in elderly patients with these mutations has not been established. Here, we describe a case of successful treatment of a patient aged >80 years with lung adenocarcinoma positive for the uncommon EGFR L861Q mutation with low-dose afatinib. An 83-year-old woman presented with cough and dyspnea. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For the elderly, 20–30 mg/day is considered to be an appropriate dose. Although most reports of low‐dose afatinib are for common mutations, there has been a study reporting that low‐dose afatinib can be safely used without reducing its efficacy in elderly patients harboring uncommon mutations 15 . In this case, an appropriate reduction in the dose of afatinib resulted in a long‐term response.…”
Section: Discussionmentioning
confidence: 96%
“…For the elderly, 20–30 mg/day is considered to be an appropriate dose. Although most reports of low‐dose afatinib are for common mutations, there has been a study reporting that low‐dose afatinib can be safely used without reducing its efficacy in elderly patients harboring uncommon mutations 15 . In this case, an appropriate reduction in the dose of afatinib resulted in a long‐term response.…”
Section: Discussionmentioning
confidence: 96%
“…Another recent case report showed the successful treatment of an 83-year-old patient with an uncommon L861Q epidermal growth factor receptor mutation. He was treated with low-dose afatinib, supporting the sensitivity of this mutation to TKI-based therapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Double mutations are detected in 14 to 18% of NSCLC samples, but their clinical significance remains not clearly characterized [ 43 , 44 ]. Kim et al concluded that patients with composite EGFR mutations have poor clinical outcomes and should be closely monitored during follow-up [ 41 ]. In our study, the follow-up was available for only one patient among three carrying composite EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been suggested that 40 mg was the recommended afatinib dose for first-line therapy [ 10 ]. A recent study has revealed that the PFS of the non-full-dose group was 12.8 months, while the PFS was 11.0 months for the full-dose group; however, the difference was not significant (HR: 1.3, 95% CI [0.9–2.0]) [ 42 ]. Yang et al have reported that afatinib 30 mg daily as an initial dose presents a similar response rate and PFS as an initial dose of 40 mg daily [ 43 ].…”
Section: Discussionmentioning
confidence: 99%